KONFLIK YURISDIKSI DAN PENEGAKAN HUKUM KEKAYAAN INTELEKTUAL DALAM RANGKA PASAR TUNGGAL - Rahmi Jened (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractIt is invisioned that ASEAN Single Market is to realize in 2015.ASEAN Single Market is what expected from the formation of ASEAN Economic community ( AEC). The basic principle of AEC is free movement of goods, services, personnel and capital. This is inherent with the objective of economic integration that is a fair competition. In relation to single market, there are trans boundary activities. It is highly possibility that international disputes over IP arise. Disputes that involve different countries with law of each their own and the need determination of choice of law /choice of forum or jurisdiction. This paper aims to discuss IP related conﬂict jurisdiction in the era of economic integration specifcally single market ASEANIntisariPada akhir 2015 diharapkan terwujud pasar tunggal ASEAN sebagai esensi perwujudan Masyarakat Ekonomi ASEAN (ASEAN Economic Community). Prinsip utama dalam rangka Economic Community adalah free movement of goods, services, skilled labours and capital. Prinsip ini inheren dengan tujuan utama integrasi ekonomi yakni persaingan sehat (fair competition). Persoalan HKI tidak hanya terbatas dalam suatu wilayah negara tertentu. Untuk itu perlu dianalisis masalah jurisdiksi pengadilan. Artikel ini akan membahas masalah konﬂik yurisdiksi dan penegakan HKI dalam rangka integrasi ekonomi dan pasar tunggal ASEAN.